Analysis of meniscal hoop strain in porcine knees - Chua, Hong Hwee (2019)
The menisci are two c-shaped cartilages located in between the femur and tibia bone. The meniscus holds a vital role in the biomechanics of the knee, absorbing shock and the ability of bearing load of the human body. As the movement rely heavily on the meniscus, degeneration of the meniscus is inevitable resulting in undesired consequences such as meniscal tears leading to the inability of load bearing and shock absorbing. Methods such as meniscal repair or meniscectomy had been greatly studied over the recent years to counter the consequences and restore the properties of a normal meniscus The main objective of this study was to measure the meniscal hoop strain generated at the peripheral rim of the meniscus at intact, with a 50% medial radial tear, 100% medial radial and repair conditions at flexion angles of 30° to 120°. A total of 2 porcine knee joints were used for this study. Porcine knees were used as they are commonly used as substitutes for human knees in various studies. The specimens were mounted on a custom-made fixture and subjected to 800 N of compressive loading on an Instron Machine. The strain results were obtained using 4 DVRTs. The strain results from the experiments showed similar trends. The effect of medial radial tear increased strain values on the anterior region and decreased in the posterior region. Strain values for repair conditions increased in the posterior region but decreased in the anterior region.